(untitled) (Upper Saddle River, NJ, 2015)
This classic text of microbiology covers molecular biology, medical biology, genetics, immunology, viruses and many other topics related to public health and disease control.
Công nghệ sinh học môi trường,Vi sinh vật đất,Vi sinh vật chuyên sâu,Ứng dụng vi sinh trong cải tạo môi trường đất
Keywords: Microbiology,Vi trùng học